2015
DOI: 10.1021/ol503728e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Glycosidase Inhibition of Australine and Its Fluorinated Derivatives

Abstract: Australine (1), 7-epi-australine (2), and their C-7-fluorinated derivatives 4 and 5 have been synthesized efficiently from D-arabinose-derived cyclic nitrone 11. Fluorination at the C-7 position enhanced the inhibition against A. niger α-glucosidase, and this constitutes the first example of fluorination substitution for a hydroxyl increasing the inhibition of any glycosidases. The enantiomers synthesized from nitrone ent-11 showed no inhibition of the corresponding enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…According to the ring substitution and saturation of the compound, alkaloids also show biological activities in glycosidase inhibition, pulmonary hypertension, and hepatotoxicity, being a very attractive and challenging target for synthetic chemists to develop new methodologies …”
Section: Introductionsupporting
confidence: 55%
“…According to the ring substitution and saturation of the compound, alkaloids also show biological activities in glycosidase inhibition, pulmonary hypertension, and hepatotoxicity, being a very attractive and challenging target for synthetic chemists to develop new methodologies …”
Section: Introductionsupporting
confidence: 55%
“…Deacetylation of both the N ‐ and O ‐acetyl groups of 10 by using Na 2 CO 3 in MeOH gave primary alcohol 11 in 97 % yield in 4 h, which upon exposure to DMSO and Ac 2 O resulted in facile oxidation14 to give aldehyde 12 in 85 % yield; this aldehyde was stable enough to be purified by column chromatography and was characterized thoroughly. Initially, zinc‐mediated allylation of aldehyde 12 was attempted 15,16. However, the reaction was found to be extremely slow and did not go to completion even after 24 h at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…According to the research of Stütz et al6b and our previous study,5c hydroxyl groups on the DMDP moiety are important for interaction of the molecule with enzymes, and should remain intact in structure modification. Based on that assumption, we recently extended our studies to australine and L ‐homoDMDP, and found that fluorination at the C‐7 position of australine enhanced inhibition against α‐glucosidase,5f whereas replacement of side chain hydroxyl groups with fluoride in L ‐homoDMDP derivatives did not show any significant influence on α‐glucosidase inhibition 5g. The above results promoted our study of radicamines, which are a special class of DMDP related iminosugars in which aryl groups constitute their side chains.…”
Section: Introductionmentioning
confidence: 86%